MobiPSE. Issue 2 (2014) - Khoi‐Nguyen Tran; Hong‐Quang Nguyen
<x xml:space="preserve"> Abstract </x> Purpose – This paper aims to solve the stated limitations through (i) exploring usages of scenarios and (ii) proposing a lightweight iterative requirement exploration process that utilizes scenarios to transform the vague ideas of the developers into concrete application's vision. The explosive growth in pervasiveness, programmability and computational capability of smartphones and tablets unlocks the possibility for many uses of technology, including end‐user development (EUD) where end‐users create applications as pragmatic tools for their work and hobbies. An extensive amount of research effort has been done to solve EUD challenges; however, the focus of such research lies mainly on designing and implementing software applications. Design/methodology/approach – Based on review on existing application of usage scenario in software application development, we proposed SRE – a scenario‐based requirement exploration method and MobiPSE – a lightweight software process that applies SRE. Two EUD projects performed by undergraduate students were used as case studies to test and fine‐tune methods. Findings – This paper proposes MobiPSE – a lightweight iterative software process that resolves around our proposed SRE method. Through case studies on MobiPSE, we confirmed that MobiPSE works in real‐life scenarios and emphasized two points: ad hoc training has limited effect and lack of technical expertise can still leave a negative impact on requirement exploration process. Research limitations/implications – Because of the limited number of case studies performed for testing and tuning purpose, the proposed methods may not be able to satisfy all cases of EUD. MobiPSE can be fine‐tuned further with additional case studies of different scale and team structure. Originality/value – This paper fulfils the need for a lightweight method for exploring requirements and ideas in a EUD project based on creating and analyzing possible usage scenarios. <ack> <x xml:space="preserve"> Acknowledgements </x> The authors would like to acknowledge that the research is funded by International University, Vietnam National University – Ho Chi Minh City under the grant number SV2013‐06‐IT. </ack>